Development of a Shock‐Wave Catheter Ablation System for Ventricular Tachyarrhythmias: Validation Study in Pigs In Vivo - Morosawa, Susumu (J Am Heart Assoc, 2019)
BACKGROUND: Although radiofrequency catheter ablation is the current state‐of‐the‐art treatment for ventricular tachyarrhythmias, it has limited success for several reasons, including insufficient lesion depth, prolonged inflammation with subsequent recurrence, and thromboembolisms due to myoendocardial thermal injury. Because shock waves can be applied to deep lesions without heat, we have been developing a shock‐wave catheter ablation (SWCA) system to overcome these fundamental limitations of radiofrequency catheter ablation. In this study, we evaluated the efficacy and safety of our SWCA system for clinical application to treat ventricular tachyarrhythmia. METHODS AND RESULTS: In 33 pigs, we examined SWCA in vivo for the following 4 protocols. First, in an epicardial substrate model (n=8), endocardial SWCA significantly decreased the sensing threshold (pre‐ versus postablation: 11.4±3.8 versus 6.8±3.6 mV; P<0.05) and increased the pacing threshold (pre‐ versus postablation: 1.6±0.8 versus 2.0±1.1 V; P<0.05), whereas endocardial radiofrequency catheter ablation failed to do so. Second, in a myocardial infarction model (n=3), epicardial SWCA of the border zone of the infarcted lesion was as effective as ablation of the normal myocardium. Third, in a coronary artery application model (n=10), direct application of shock waves to the epicardial coronary arteries caused no adverse effects in either the acute or chronic phase. Fourth, with an epicardial approach (n=8), we found that 90 shots per site provided an ideal therapeutic condition to create deep lesions with less superficial damage. CONCLUSIONS: These results indicate that our new SWCA system is effective and safe for treatment of ventricular tachyarrhythmias with deep arrhythmogenic substrates.